Pengaruh Metode Demonstrasi Terhadap Perilaku Sosial Anak dikelompok B TK Negeri Harapan Bangsa Desa Guntarano - Khairunnisa; Andi Agusniatih; Jane Mariem Monepa; Durrotunnisa (Jurnal Pelita PAUD, 2025)
Social behavior is an important aspect in child development. One method that can be used is the demonstration method. The purpose of this study is to determine the effect of the demonstration method on children's social behavior. This study uses a quantitative approach and experimental research type. The research subjects were 14 children in group B. Data collection through observation, interviews, and documentation. Based on the results of observations before and after being given treatment, the aspect of respect for the BSB category from 21% to 50%, the second category BSH from 29% to 36%, the third category MB 36% to 14% and the third category BB from 14% to 0%. While the second aspect of cooperation for the BSB category from %0 to 57%, the BSH category from 57% to 36%, the MB category from 36% to 14%, and the BB category from 7% to 0%. And the third aspect of mutual assistance for the BSB category from 0% to 57%, the BSH category from 43% to 36%, the MB category from 43% to 7% and the BB category from 14% to 0%. In addition, the t-value is 14.381 with a significance of 0.000 because it is <0.05, so it can be concluded that Ho is rejected and H1 is accepted, meaning there is an Influence of the Demonstration Method on the Social Behavior of Children in Group B of Harapan Bangsa State Kindergarten.